189k views
5 votes
What is the following product? Assume x ≥ 0

\sqrt[3]{x^{2} } . \sqrt[4]{x^{3} }


A. x\sqrt{x}

B. \sqrt[12]{x^{5} }

C. x(\sqrt[12]{x^{5} } )

D. x6

2 Answers

3 votes

Answer:

its c

Explanation:

User Fishstick
by
5.3k points
2 votes

For this case we must multiply the following expression:


\sqrt [3] {x ^ 2} * \sqrt [4] {x ^ 3}

By definition of properties of otencias and roots we have:


\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}

We rewrite the terms of the expression:


\sqrt [3] {x ^ 2} = (x ^ 2) ^ {\frac {1} {3}} = (x ^ 2) ^ {\frac {4} {12}}\\\sqrt [4] {x ^ 3} = (x ^ 3) ^ {\frac {1} {4}} = (x ^ 3) ^ {\frac {3} {12}}

So, we have:


(x ^ 2) ^ {\frac {4} {12}} * (x ^ 3) ^ {\frac {3} {12}} =

Applying the above definition we have:


\sqrt [12] {(x ^ 2) ^ 4} * \sqrt [12] {(x ^ 3) ^ 3} =

We multiply the exponents:


\sqrt [12] {x ^ 8} * \sqrt [12] {x ^ 9} =

We combine using the product rule for radicals.


\sqrt [12] {x ^ 8 * x ^ 9} =

By definition of multiplication properties of powers of the same base, we put the same base and add the exponents:


\sqrt [12] {x ^ {8 + 9}} =\\\sqrt [12] {x ^ {17}} =\\\sqrt [12] {x ^ {12} * x ^ 5} =\\x \sqrt [12] {x ^ 5}

Answer:

Option C

User Collin Flynn
by
5.1k points